Sodium-ion battery positive electrode material and preparation method thereof, positive electrode plate, battery and electric device
By covering the metal phosphate coating of aluminum and sodium elements on the matrix of the positive electrode material of the sodium ion battery, the problem of poor electrochemical performance of sodium ion battery is solved, high capacity and cycle stability are achieved, and the rate performance is improved. Conductivity.
Patent Information
- Application Number
- CN202310766018.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-26
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-06-26
AI Technical Summary
The poor electrochemical performance of sodium ion batteries in terms of capacity, rate performance and stability limits their practical application.
The sodium-containing positive electrode material matrix is coated with metal phosphate coating, including aluminum and sodium elements, and the residual alkali content on the substrate surface is reduced through the sintering process, forming a coating with good conductivity, improving the migration efficiency of sodium ions and Rate performance.
The high capacity and cycle stability of sodium ion batteries are achieved, the rate performance and conductivity of the battery are improved, and the migration efficiency of sodium ions is improved.
Smart Images

Figure CN119208548A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology, and specifically relates to a sodium ion battery positive electrode material and a preparation method thereof, a positive electrode sheet, a battery, and an electrical device. Background Art
[0002] Sodium-ion batteries are secondary batteries that rely mainly on the movement of sodium ions between the positive and negative electrodes to work. Secondary batteries represented by sodium-ion batteries have been used in energy storage power systems (such as hydropower, thermal, wind and solar power stations, etc.), as well as electric vehicles, aerospace and other fields. Compared with lithium-ion batteries, sodium-ion batteries have significant cost advantages in terms of raw materials, especially for positive electrode materials, which account for a large proportion of the cost. The reserves of sodium salts, which are the main components of sodium positive electrode materials, are more abundant, and the price of sodium salts is much lower than that of lithium salts used in lithium-ion battery positive electrode materials, which makes the cost of sodium positive electrode materials lower than that of lithium batteries. However, sodium-ion batteries have poor electrochemical properties in terms of capacity, rate performance and stability, which limits their practical applications. Summary of the invention
[0003] In view of the above-mentioned problems, the purpose of this application is to provide a sodium ion battery positive electrode material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device. The battery prepared with the sodium ion battery positive electrode material has the characteristics of high battery capacity and good cycle stability.
[0004] In the first aspect, the present application provides a sodium ion battery positive electrode material, comprising: a sodium-containing positive electrode material substrate, and a coating layer coated on at least part of the surface of the sodium-containing positive electrode material substrate; wherein the coating layer comprises a metal phosphate, and the metal phosphate contains at least sodium and aluminum elements. In the sodium ion battery positive electrode material of the present application, a metal phosphate containing at least sodium and aluminum elements is used as a coating layer component and distributed on the substrate, which not only reduces the residual alkali content on the surface of the substrate, but also makes the coating layer conductive, and promotes the migration of sodium ions while stabilizing the interface.
[0005] In some embodiments of the present application, the chemical formula of the metal phosphate is Na x1 Al y1 L y2 P z O s, wherein L includes at least one of Ca, Mg, Fe, Ti, V, Cr, Mn, Ni, La, Ce, Sr, Cu, Zn, Y, Zr, Nb and Mo; x1>0, y1>0, y2≥0, z>0, s>0. The coating layer includes a metal phosphate having aluminum, sodium and the optional metal element L, so that the residual alkali with poor conductivity on the substrate is converted into a conductive network of metal oxide-phosphorus oxide, thereby improving the conductivity of the positive electrode material. Optionally, the chemical formula of the metal phosphate is NaAl y1 L y2 P z O2, and 0<y1<1, 0≤y2<1, 0<z<1.
[0006] In some embodiments of the present application, in the coating layer, the molar ratio of aluminum to phosphorus in the metal phosphate can be 0.1-10, which can improve the stability of the coating layer on the surface of the substrate. Optionally, the molar ratio of aluminum to phosphorus is 0.1-0.6, thereby making the coating layer have a higher stability and further improving the conductivity of the positive electrode material.
[0007] In some embodiments of the present application, the coating layer may have a thickness of 1 nm to 100 nm. Optionally, the coating layer has a thickness of 5 nm to 25 nm, thereby reducing the migration path of sodium ions and improving rate performance while ensuring the coating effect.
[0008] In some embodiments of the present application, the sodium-containing positive electrode material matrix may include a layered oxide, the chemical formula of the layered oxide is Na x2 Mn a Fe b M c A d O 2-e+f Q e , wherein M includes at least one of Cu, Ni, Li, Ti, Zr, K, La, Ce, Sr, Sb, Nb, Mg, Ca, Mo, Zn, Cr, W, Bi, Sn, Ge and Al; A includes at least one of Si, P, B, S and Se; Q includes at least one of F, Cl and N; a>0, b>0, c≥0, d≥0, and a+b+c+d=1, x2≥0.66, 0≤e≤0.1, -0.1≤f≤0.
[0009] In some embodiments of the present application, the layered oxide is an O3-type layered oxide. In the process of preparing the positive electrode material, there is more residual alkali on the surface of the O3 layered oxide, and sufficient residual alkali can provide a sodium source for the coating layer during the sintering process, thereby forming a coating layer containing sodium elements, and converting the residual alkali with poor conductivity into a coating layer with good conductivity, which can improve the rate performance of the material.
[0010] In some embodiments of the present application, in the sodium ion battery positive electrode material, the mass ratio of the coating layer to the sodium-containing positive electrode material matrix can be (0.1-10) : 100. Optionally, the mass ratio of the coating layer to the sodium-containing positive electrode material matrix is (0.2-2) : 100, thereby further improving the migration efficiency of sodium ions and improving the rate performance of the material while ensuring the coating effect.
[0011] In a second aspect, the present application provides a method for preparing the positive electrode material of a sodium ion battery, the method comprising: mixing and sintering a coating layer raw material including an aluminum source and a phosphorus source with a sodium-containing positive electrode material matrix. The method can reduce the residual alkali generated by the sodium-containing positive electrode material matrix, and during the sintering process, the residual alkali is converted into a conductive network containing Na2O-P2O5, and Na2O-P2O5 is compounded with an aluminum-containing metal oxide, thereby forming a metal phosphate containing at least sodium and aluminum elements coated on the surface of the matrix, and obtaining a sodium ion battery positive electrode material.
[0012] In some embodiments of the present application, the aluminum source includes at least one of aluminum oxide and aluminum hydroxide.
[0013] In some embodiments of the present application, the phosphorus source includes at least one of diammonium phosphate and ammonium metaphosphate.
[0014] In some embodiments of the present application, the aluminum source is aluminum oxide, and the median particle size of the aluminum oxide is 10nm-50nm; the phosphorus source is ammonium dihydrogen phosphate, and the median particle size of the ammonium dihydrogen phosphate is 1μm-15μm. Thus, the material of the formed coating layer can be more evenly dispersed on the surface of the substrate, improving the electrochemical performance of the positive electrode material.
[0015] In some embodiments of the present application, the coating layer raw material further includes at least one of titanium oxide (TiO2) and calcium oxide (CaO). The addition of CaO can further form NaCaPO4 in the coating layer. The presence of NaCaPO4 can effectively remove water from the electrolyte and inhibit the influence of HF during the battery cycle. The specific reaction is as follows:
[0016] NaCaPO4+HF→CaHPO4+NaF
[0017] 2NaCaPO4+H2O→2CaHPO4+Na2O;
[0018] The introduction of TiO2 can form NaTi2(PO4)3 solid electrolyte on the surface of the matrix, which not only has high ionic conductivity but also excellent thermal stability.
[0019] In some embodiments of the present application, the sintering temperature may be 100° C.-1000° C. Optionally, the sintering temperature is 300° C.-600° C., thereby promoting the phosphorus source to react with the residual alkali in the substrate and making the formed coating layer more closely contact with the substrate.
[0020] In some embodiments of the present application, the sintering time is 1 hour to 24 hours. Optionally, the sintering time is 3 hours to 10 hours, thereby further preventing the diffusion of lattice sodium to the surface while ensuring the coating effect.
[0021] In some embodiments of the present application, the mixing includes: first mixing the components in the coating layer raw material to obtain a composite coating agent; and then second mixing the composite coating agent with a sodium-containing positive electrode material matrix.
[0022] Optionally, the first mixing conditions include: a rotation speed of 800 rpm-1200 rpm and a time of 20 min-60 min. Thus, a composite coating agent with components uniformly dispersed can be obtained, thereby improving the coating effect.
[0023] Optionally, the second mixing conditions include: a rotation speed of 800 rpm-1000 rpm, and a time of 20 min-30 min.
[0024] In a third aspect, the present application provides a positive electrode plate, comprising the sodium ion battery positive electrode material described in the first aspect of the present application or the sodium ion battery positive electrode material prepared by the method described in the second aspect of the present application.
[0025] In a fourth aspect, the present application provides a battery comprising the sodium ion battery positive electrode material described in the first aspect of the present application or the sodium ion battery positive electrode material prepared by the method described in the second aspect of the present application, or comprising the positive electrode sheet described in the third aspect of the present application.
[0026] In a fifth aspect, the present application provides an electrical device, comprising the battery described in the fourth aspect of the present application.
[0027] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only used to illustrate the preferred embodiments and are not to be considered as limiting the present application. In the accompanying drawings:
[0029] Figure 1 This is a scanning electron microscope image of the sodium ion battery positive electrode material prepared in Example 1;
[0030] Figure 2 This is a scanning electron microscope image of the sodium-containing positive electrode material of Comparative Example 1;
[0031] Figure 3 This is a comparison chart of the cycle performance of sodium ion batteries prepared using the positive electrode materials of Example 1 and Comparative Example 1;
[0032] Figure 4 A schematic diagram of the structure of a battery according to one embodiment of the present application;
[0033] Figure 5 This is a schematic structural diagram of a battery module according to an embodiment of the present application;
[0034] Figure 6 A schematic diagram of the structure of a battery pack according to an embodiment of the present application;
[0035] Figure 7 for Figure 6 Exploded diagram of
[0036] Figure 8 A schematic diagram of an embodiment of an electrical device using a battery as a power source.
[0037] Description of reference numerals:
[0038] 1: Battery; 2: Battery module; 3: Battery pack; 4: Upper case; 5: Lower case. DETAILED DESCRIPTION
[0039] The present application is further described below in conjunction with specific implementations. It should be understood that these specific implementations are only used to illustrate the present application and are not used to limit the scope of the present application.
[0040] In this application, the reference to "embodiment" means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application can be combined with other embodiments.
[0041] "Scope" disclosed in the present application is defined in the form of lower limit and / or upper limit, and a given range is defined by selecting a lower limit and / or an upper limit, and the selected lower limit and / or the rear upper limit define the boundary of a special range. The scope defined in this way can be including or excluding end values, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form a scope that is not clearly recorded, and any lower limit can be combined with other lower limits to form a scope that is not clearly recorded, and any upper limit can be combined with any other upper limit to form a scope that is not clearly recorded. In addition, each separately disclosed point or single numerical value itself can be used as a lower limit or upper limit and any other point or single numerical value combination or with other lower limits or upper limits to form a scope that is not clearly recorded.
[0042] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0043] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0044] Unless otherwise specified, the terms "include", "comprising", "including", "containing", and "having" mentioned in this application may be open-ended or closed-ended. For example, the terms "include", "comprising", "containing", "containing", and "having" may indicate that other components not listed may also be included or contained, or may only include or contain the listed components. In addition, in this application, the terms "plurality", "multiple", and "at least one" refer to more than two. "Above" and "below" include the number itself. For example, "more than two" includes two itself, such as two, three, four or more.
[0045] If there is no special explanation, in this application, the term "and / or" is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0046] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as those commonly understood by technicians in the technical field of this application; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and any variations thereof are intended to cover non-exclusive inclusions. Unless otherwise specified, the terms used in this application have the well-known meanings commonly understood by those skilled in the art. Unless otherwise specified, the numerical values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).
[0047] Although the performance of sodium ion battery cathode materials is similar to that of lithium ion cathode materials, their interfaces are more sensitive to air and electrolyte during storage and use. + ) migration, resulting in a decrease in the electrochemical performance of the battery, and the sodium ion positive electrode material (especially the layered oxide) has a serious residual alkali on the surface, which also leads to a decrease in capacity. Therefore, it is necessary to modify the sodium ion positive electrode material.
[0048] Accordingly, the first aspect of the present application provides a sodium ion battery positive electrode material, comprising: a sodium-containing positive electrode material substrate, and a coating layer coated on at least part of the surface of the sodium-containing positive electrode material substrate. The coating layer includes a metal phosphate containing at least sodium and aluminum elements. In the sodium ion battery positive electrode material of the present application, the coating layer containing the metal phosphate can play a role in shielding air and electrolyte. The coating layer not only reduces the residual alkali content on the surface of the substrate, but also has conductivity. While stabilizing the interface, it promotes the migration of sodium ions and improves the rate performance of the battery. In the present application, "metal phosphate" refers to a complex having a metal element, a phosphorus element and an oxygen element. Each element in the complex may exist in the form of multiple components. Due to the differences in the coating agent ratio, the alkali content on the substrate surface and the preparation conditions, these components may include, but are not limited to, oxides of metal elements (such as Al2O3, TiO2), oxygen-containing salts of metal elements (such as Na2TiO3), phosphorus oxides (such as P2O5), various inorganic substances composed of metal elements, phosphorus elements and oxygen elements (such as NaPO3, NaTi2(PO4)3, NaAl 0.4 Ti 0.2 PO4).
[0049] In some embodiments, the chemical formula of the metal phosphate is Na x1 Al y1 L y2 P z O s, wherein L includes at least one of Ca, Mg, Fe, Ti, V, Cr, Mn, Ni, La, Ce, Sr, Cu, Zn, Y, Zr, Nb and Mo; x1>0, y1>0, y2≥0, z>0, s>0. The coating layer includes a metal phosphate having aluminum, sodium and the optional metal element L, so that the residual alkali with poor conductivity on the substrate is converted into a conductive network of metal oxide (including aluminum oxide and optional metal L oxide)-phosphorus oxide, thereby improving the conductivity of the positive electrode material. Na x1 Al y1 L y2 P z O s The net charge of Na is zero. The net charge of Na is zero. x1 Al y1 L y2 P z O s In the system composed of, the algebraic sum of the positive charge number of sodium ions, aluminum ions, phosphorus ions and metal L ions and the negative charge number of oxygen ions is zero. For example, when y2=0, the net charge is zero, indicating that x1, y1, z and s satisfy the relationship x1+3y1+5z=2s; when y2>0, the net charge is zero, indicating that x1, y1, y2, z and s satisfy the relationship x1+3y1+my2+5z=2s, where m represents the positive charge number of metal L ions, for example, when L is Mg, the positive charge number of L ions is m=2. The net charge can be measured by X-ray photoelectron spectrometer (XPS).
[0050] In some embodiments, in the coating layer, the molar ratio of aluminum to phosphorus in the metal phosphate is 0.1-10, such as 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 3.5, 4, 5, 8, 9, etc.; thus, the coating layer on the surface of the substrate has high stability. Optionally, the molar ratio of aluminum to phosphorus in the metal phosphate is 0.1-0.6, which can further improve the conductivity of the positive electrode material while ensuring the coating stability.
[0051] In the present application, when the metal phosphate is represented by the chemical formula involved, the molar ratio of aluminum element to phosphorus element is equal to the ratio of y1 to z in the corresponding subscripts of Al and P respectively.
[0052] In some specific embodiments, the chemical formula of the metal phosphate is NaAl y1 L y2 P zO2, wherein 0<y1<1, 0≤y2<1, 0<z<1. In this embodiment, the relative molar amounts of Al, L, and P are expressed with Na as the reference; wherein y1 may optionally satisfy the relationship 0.01<y1<0.9, and more preferably 0.05<y1<0.3; y2 may optionally satisfy the relationship 0≤y2<0.5, and more preferably 0≤y2<0.3; z may optionally satisfy the relationship 0.1<z<0.9, and more preferably 0.2<z<0.6.
[0053] In some embodiments, the coating layer may have a thickness of 1 nm to 100 nm, such as 1 nm, 2 nm, 3 nm, 5 nm, 10 nm, 11 nm, 15 nm, 18 nm, 20 nm, 25 nm, 30 nm, 40 nm, 45 nm, 50 nm, 60 nm, etc. Optionally, the coating layer has a thickness of 5 nm to 25 nm. Thus, while ensuring the coating effect, the migration path of the sodium ions is reduced and the rate performance is improved. The thickness of the coating layer can be obtained by transmission electron microscopy analysis.
[0054] The present application does not particularly limit the sodium-containing positive electrode material matrix, and can be various sodium ion positive electrode materials well known in the art, for example, it can include at least one of layered oxides, Prussian blue compounds and polyanionic compounds. In addition, the present application is particularly suitable for improving the electrochemical properties of sodium-containing positive electrode materials with high residual alkali content. From this perspective, optionally, the sodium-containing positive electrode material is a layered oxide. The layered oxide generally includes sodium-containing transition metal layered oxide compounds.
[0055] In some embodiments, the chemical formula of the layered oxide is Na x2 Mn a Fe b M c A d O 2-e+f Q e, a>0, b>0, c≥0, d≥0, and a+b+c+d=1, x2≥0.66, 0≤e≤0.1; wherein, M includes at least one of Cu, Ni, Li, Ti, Zr, K, La, Ce, Sr, Sb, Nb, Mg, Ca, Mo, Zn, Cr, W, Bi, Sn, Ge and Al, and can be selected as at least one of Ni, Cu, Zn, Ti, Zr, Ca and Al; A includes at least one of Si, P, B, S and Se; Q includes at least one of F, Cl and N; a>0, 0.1<a≤0.6 can be selected; b>0, 0.1<b≤0.6 can be selected; c≥0, 0≤c≤0.9 can be selected, d≥0, and a+b+c+d=1; x2≥0.66, 0.66≤x2≤1 can be selected; 0≤e≤0.1, -0.1≤f≤0. It should be understood that when Q is doped at the O position in the layered oxide, lattice oxygen release occurs during the high-temperature synthesis process, making the sum of the subscripts of O and Q in the chemical formula 2+f less than 2.
[0056] In some embodiments, the layered oxide is an O3-type layered oxide. In the process of preparing the positive electrode material for the sodium ion battery, since there is more residual alkali on the surface of the O3 layered oxide material, the residual alkali has poor conductivity, and sufficient residual alkali will be converted into a coating layer with good conductivity during the sintering process, which is beneficial to improving the rate performance of the material.
[0057] In some embodiments, the particle size D of the sodium-containing positive electrode material matrix is V 50 is 1μm-15μm, such as 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, etc. Matrix particle size D V 50 can be measured by laser particle size analyzer.
[0058] In the present application, the mass of the coating layer can be determined according to the mass of the sodium-containing positive electrode material matrix. In some embodiments, in the sodium ion battery positive electrode material, the mass ratio of the coating layer to the sodium-containing positive electrode material matrix is (0.1-10):100, for example, 0.1:100, 0.2:100, 0.3:100, 0.4:100, 0.5:100, 0.6:100, 0.7:100, 0.8:100, 0.9:100, 1:100, 1.1:100, 1.2:100, 1.5:100, 1.8:100, 2:100, 3:100, 4:100, 5:100, 6:100, 7:100, 8:100, 9:100, etc. Optionally, the mass ratio of the coating layer to the sodium-containing positive electrode material matrix is (0.2-2):100, which can further improve the migration efficiency of sodium ions and improve the rate performance of the material while ensuring the coating effect.
[0059] The second aspect of the present application provides a method for preparing the positive electrode material of a sodium ion battery, the method comprising: mixing and sintering a coating layer raw material including an aluminum source and a phosphorus source with a sodium-containing positive electrode material matrix. The method can reduce the residual alkali generated by the sodium-containing positive electrode material matrix, and during the sintering process, the residual alkali is first converted into a conductive network having Na2O-P2O5, and Na2O-P2O5 is compounded with an aluminum-containing metal oxide, thereby forming a metal phosphate containing at least sodium and aluminum elements coated on the surface of the matrix, and obtaining a sodium ion battery positive electrode material.
[0060] According to the method of the present application, the sodium-containing positive electrode material matrix can be obtained commercially or prepared by methods well known in the art, and the present application has no particular restrictions on this. In some embodiments, the sodium-containing positive electrode material matrix is Na x2 Mn a Fe b M c A d O 2-e+f Q e, which is prepared by a method comprising the following steps: a transition metal source (including a manganese source, an iron source, and an optional M source and an optional A source) and a sodium source are mixed uniformly according to the component ratio of the chemical formula to obtain a sodium-containing positive electrode material precursor, and the precursor is calcined, cooled and crushed. It should be understood that in order to avoid the volatilization of sodium at high temperature, the relative amount of the sodium source and each transition metal source can be slightly higher than the ratio shown in the chemical formula, for example, 3% higher. The transition metal source may include an oxide of a transition metal. As an example, the transition metal source includes iron oxide, manganese oxide, nickel oxide, etc., and the sodium source includes one or more of Na2CO3, NaHCO3, NaOH and Na2O2. The calcination temperature may be 500°C-1300°C, for example, 500°C, 600°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, etc. The calcination time can be 5h-20h, for example 5h, 6h, 7h, 8h, 9h, 10h, 12h, 14h, 15h, 18h, 20h, etc. The crystalline structure of the prepared sodium-containing positive electrode material matrix can be measured by X-ray diffractometer (XRD), and the elemental composition can be measured by inductively coupled plasma atomic emission spectrometry (ICP).
[0061] According to the method of the present application, in the coating layer raw material, the aluminum source may include a solid aluminum source, and the solid aluminum source may generally be selected from various aluminum-containing compounds that can be converted into aluminum oxide during sintering. In some embodiments, from the perspective of easy availability of raw materials, the aluminum source includes at least one of aluminum oxide and aluminum hydroxide.
[0062] According to the method of the present application, in the coating layer raw material, the phosphorus source may include a solid phosphorus source, and the solid phosphorus source may generally be a phosphorus-containing compound that can be converted into phosphorus oxide during sintering. As an example, the phosphorus source includes one or more of an acidic solid phosphorus source and a neutral solid phosphorus source. Optionally, the phosphorus source includes at least one of diammonium phosphate and ammonium metaphosphate.
[0063] In some specific embodiments, the aluminum source is aluminum oxide, and the phosphorus source is ammonium dihydrogen phosphate, wherein the median particle size of the aluminum oxide can be 10nm-50nm, such as 10nm, 15nm, 20nm, 22nm, 25nm, 30nm, 35nm, 40nm, 45nm, etc.; the median particle size of ammonium dihydrogen phosphate can be 1μm-15μm, such as 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 12μm, 13μm, 14μm, 15μm, etc. The nano-scale aluminum oxide and micro-scale ammonium dihydrogen phosphate are evenly mixed with the matrix. As an example, in the low-temperature sintering stage, the ammonium dihydrogen phosphate is prone to the following reactions:
[0064] 190℃: NH4H2PO4→H3PO4+NH3↑
[0065] 215℃: 2H3PO4→H4P2O7+H2O
[0066] 300℃: H4P2O7→2HPO3+H2O
[0067] HPO3+Na2O→Na x3 (PO) y +H2O↑
[0068] HPO3+NaOH→Na x3 (PO) y +H2O
[0069] HPO3+Na2CO3→Na x3 (PO) y +CO2+H2O↑;
[0070] Through the above decomposition and acid-base neutralization reaction, the residual alkali (including Na2O, NaOH and Na2CO3) with poor conductivity on the substrate is converted into a Na2O-P2O5 conductive network. Moreover, Na2O-P2O5 is further compounded with Al2O3, so that the formed metal phosphate is coated on the surface of the substrate to stabilize the interface and also give the material better electrochemical properties. In addition, using ammonium dihydrogen phosphate as the raw material, ammonium dihydrogen phosphate will decompose into phosphoric acid when heated, and has a stronger reaction activity with residual alkali, which can more effectively remove the residual alkali.
[0071] In some embodiments, the coating layer raw material consists of the aluminum source and the phosphorus source. In other embodiments, the coating layer raw material consists of the aluminum source, the phosphorus source and an L source. The L source can be a solid L source, for example, including an oxide containing the element L.
[0072] In some embodiments, the coating layer raw material further includes at least one of titanium oxide and calcium oxide.
[0073] As an example, the median particle size of titanium oxide is 20 μm-50 μm, such as 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, etc.
[0074] As an example, the median particle size of calcium oxide is 20 μm-50 μm, such as 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, etc.
[0075] In some embodiments, the mixing includes: first mixing the components (aluminum source, phosphorus source and optional L source) in the coating layer raw material to obtain a composite coating agent; and second mixing the composite coating agent with the sodium-containing positive electrode material matrix. The two-stage mixing can improve the dispersion uniformity of the coating raw material in the matrix.
[0076] In some embodiments, the first mixing can be performed on a ball mill. Optionally, the first mixing conditions include: a rotation speed of 800 rpm-1200 rpm, and a time of 20 min-60 min. Thus, a composite coating agent with each component uniformly dispersed can be obtained.
[0077] In some embodiments, the second mixing can be performed on a mixer (e.g., a mechanical fusion machine). Optionally, the second mixing conditions include: a rotation speed of 800 rpm-1000 rpm, and a time of 20 min-30 min. Thus, while ensuring the dispersion effect of the composite coating agent in the sodium-containing positive electrode material matrix, energy consumption is reduced.
[0078] According to the method of the present application, the sintering of the precursor obtained after mixing can be carried out in an oxygen-containing atmosphere, such as oxygen or air, and a coating layer including a phosphate containing at least aluminum (Al) and sodium (Na) is obtained by sintering. The elemental composition of the coating layer can be obtained by XPS element valence analysis combined with ICP analysis.
[0079] In some embodiments, the sintering temperature is 100°C-1000°C, such as 100°C, 150°C, 190°C, 200°C, 210°C, 215°C, 280°C, 300°C, 350°C, 400°C, 500°C, 600°C, 700°C, 750°C, 800°C, 900°C, 1000°C, etc. Optionally, the sintering temperature is 300-600°C, thereby promoting the phosphorus source to react with the residual alkali in the matrix while making the formed coating layer contact more closely with the matrix. In particular, when the phosphorus source is ammonium dihydrogen phosphate, the sintering temperature is controlled within this range. On the one hand, the volatilization rate of ammonium dihydrogen phosphate can be controlled to effectively react with the residual alkali, and on the other hand, the Al2O3-P2O5 crystallization formed due to the excessively high reaction temperature can be avoided (the performance of the crystalline coating layer is worse than that of the amorphous coating layer). In addition, controlling the sintering temperature within this range can further prevent the excessively high temperature from causing more coating agent to be doped into the interior of the matrix, resulting in a decrease in the coating effect (this problem leads to increased Na volatilization and capacity loss).
[0080] In some embodiments, the sintering time is 1h-24h, such as 1h, 2h, 2.5h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 22h, 24h, etc. Optionally, the sintering time is 3h-10h, which can ensure the coating effect while avoiding the diffusion of lattice sodium to the surface of the matrix due to its own instability to form new residual alkali.
[0081] In some specific embodiments, the method comprises the following steps:
[0082] S1: providing sodium-containing positive electrode material;
[0083] S2: mixing the coating layer raw materials including nano-alumina, micron-sized ammonium dihydrogen phosphate and an optional micron-sized L source uniformly through a ball mill to obtain a composite coating agent;
[0084] S3: The sodium-containing positive electrode material and the composite coating agent are mixed evenly by a mechanical fusion machine, placed in a muffle furnace for sintering, and air is introduced during the sintering process. After the sintering is completed, the mixture is cooled to room temperature.
[0085] The third aspect of the present application provides a positive electrode plate, comprising the sodium ion battery positive electrode material described in the first aspect of the present application or the sodium ion battery positive electrode material prepared by the method described in the second aspect of the present application.
[0086] In some embodiments, the positive electrode plate includes a positive electrode current collector and a positive electrode film layer disposed on at least one side of the positive electrode current collector, and the positive electrode film layer contains the sodium ion battery positive electrode material.
[0087] In the present application, the positive electrode current collector may be, for example, a metal foil or a composite current collector. The metal foil may be, for example, an aluminum foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one side of the polymer base layer, wherein the material of the metal layer includes, but is not limited to, aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, etc.; the polymer material of the polymer base layer may be, for example, polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0088] In some embodiments, the positive electrode material of the sodium ion battery is used as the positive electrode active material in the positive electrode film layer. In addition to the positive electrode material, the positive electrode film layer may also optionally contain a conductive agent and / or a binder. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers; the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0089] The present application does not particularly limit the preparation method of the positive electrode sheet, and the positive electrode sheet can be prepared by referring to the existing method. For example, the positive electrode slurry is coated on the positive electrode current collector, and the positive electrode sheet is formed by drying and cold pressing. The positive electrode slurry can be formed by dispersing the components such as the positive electrode material of the sodium ion battery, the optional conductive agent, and the optional binder in a solvent (such as N-methylpyrrolidone) and stirring them evenly.
[0090] In addition, the positive electrode plate of the present application does not exclude other additional functional layers in addition to the positive electrode film layer. For example, the positive electrode plate may also include a conductive primer layer (e.g., composed of a conductive agent and a binder) disposed between the positive electrode current collector and the positive electrode film layer. For another example, the positive electrode plate may also include a protective layer covering the surface of the positive electrode film layer.
[0091] The fourth aspect of the present application provides a battery, comprising the sodium ion battery positive electrode material described in the first aspect of the present application or the sodium ion battery positive electrode material prepared by the method described in the second aspect of the present application, or including the positive electrode sheet described in the third aspect of the present application.
[0092] In the present application, the battery may be a secondary battery. It is understandable that the secondary battery may be a sodium ion battery. In some embodiments, the secondary battery further comprises a negative electrode sheet, a separator and an electrolyte. During the battery charge and discharge process, active ions are embedded and extracted back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, which can prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0093] [Negative electrode]
[0094] In some embodiments, the negative electrode sheet may include a negative electrode current collector and a negative electrode film layer disposed on at least one side of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode material.
[0095] In some embodiments, the negative electrode current collector may include a metal foil or a composite current collector. The metal foil is, for example, a copper foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one side of the polymer base layer. Among them, the material of the metal layer includes, but is not limited to, copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, etc., and the polymer material of the polymer base layer includes, but is not limited to, polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0096] In the present application, the negative electrode material may include a negative electrode active material for a secondary battery well known in the art. For example, the negative electrode active material includes at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may include at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may include at least one of elemental tin, tin oxide compounds, and tin alloys.
[0097] In some embodiments, the negative electrode film layer may further optionally include a binder. The binder may include, for example, at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), carboxymethyl cellulose (CMC), and carboxymethyl chitosan (CMCS).
[0098] In some embodiments, the negative electrode film layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0099] In some embodiments, the negative electrode film layer may also optionally contain other additives, such as a thickener. Specific examples of thickeners include, but are not limited to, sodium carboxymethyl cellulose (CMC-Na).
[0100] The present application does not specifically limit the preparation method of the negative electrode sheet, and the negative electrode sheet can be prepared by referring to the existing method. For example, the negative electrode components such as the negative electrode material, the conductive agent, and the binder are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is then coated on the negative electrode current collector, and the negative electrode sheet is obtained by drying, cold pressing, etc.
[0101] [Electrolyte]
[0102] In the present application, the electrolyte can be selected with reference to existing secondary batteries. In some embodiments, the electrolyte comprises an organic solvent, a sodium salt and an optional additive. The sodium salt includes, but is not limited to, at least one of NaPF6, NaClO4, NaBCl4, NaSO3CF3 and Na(CH3)C6H4SO3. The organic solvent includes, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0103] In some embodiments, the additives in the electrolyte may include negative electrode film-forming additives and positive electrode film-forming additives; they may also include additives that can improve certain properties of the battery, such as additives that improve the overcharge performance of the battery, additives that improve the high temperature or low temperature performance of the battery, etc. As an example, the additives may include, but are not limited to, at least one of vinylene carbonate (VC), vinyl carbonate (VEC), vinyl sulfate (DTD), propylene sulfate, vinyl sulfite (ES), 1,3-propane sultone (PS), 1,3-propylene sultone (PST), sulfonate cyclic quaternary ammonium salt, succinic anhydride, succinonitrile (SN), adiponitrile (AND), tris(trimethylsilyl) phosphate (TMSP) and tris(trimethylsilyl) borate (TMSB).
[0104] [Isolation film]
[0105] In the present application, the isolation membrane is arranged between the positive electrode plate and the negative electrode plate, and mainly plays the role of preventing the positive and negative electrodes from short-circuiting, while allowing active ions to pass through. The present application has no particular restrictions on the type of isolation membrane, and various porous structure isolation membranes well known in the art can be selected. In some embodiments, the material of the isolation membrane may include at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. In addition, the isolation membrane can be a single-layer film or a multi-layer composite film. When the isolation membrane is a multi-layer composite film, the materials of each layer are the same or different.
[0106] In some embodiments, a ceramic coating and / or a metal oxide coating is further disposed on the isolation membrane.
[0107] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0108] The present application has no particular limitation on the shape of the battery, which may be cylindrical, square, or any other shape. Figure 4 The battery 1 is a square structure as an example. The number of electrode assemblies contained in the battery can be one or more, which can be adjusted according to needs.
[0109] In some embodiments, the battery may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.
[0110] In some embodiments, the outer package may include a shell and a cover plate. The shell may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell has an opening connected to the receiving cavity, and the cover plate can be covered on the opening to close the receiving cavity. The electrode assembly can be encapsulated in the receiving cavity.
[0111] In some embodiments, the outer packaging of the battery is a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc.
[0112] In other embodiments, the outer packaging of the battery is a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.
[0113] In some embodiments, the batteries may be assembled into a battery module. The battery module may contain multiple batteries, and the specific number may be adjusted according to the application and capacity of the battery module.
[0114] Figure 5 2 is an example of a battery module 2. Figure 5 In the battery module 2, the multiple batteries 1 may be arranged in sequence along the length direction of the battery module 2. Of course, they may also be arranged in any other manner. The multiple batteries 1 may further be fixed by fasteners.
[0115] The battery module 2 may further include a housing having a housing space, and the plurality of batteries 1 may be housed in the housing space.
[0116] In some embodiments, the battery modules may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0117] Figure 6 and 7 The battery pack 3 is used as an example. Figure 6 and 7The battery pack 3 may include a battery box and a plurality of battery modules 2 disposed in the battery box. The battery box includes an upper box body 4 and a lower box body 5. The upper box body 4 can cover the lower box body 5 and form a closed space for accommodating the battery modules 2. The plurality of battery modules 2 can be arranged in the battery box in any manner.
[0118] The fifth aspect of the present application provides an electrical device, comprising the battery described in the fourth aspect of the present application.
[0119] In the present application, the power-consuming device may include, but is not limited to, mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. The power-consuming device may select a battery according to its usage requirements.
[0120] Figure 8 The power consumption device is used as an example. The power consumption device may be a pure electric vehicle, a hybrid electric vehicle or a plug-in hybrid electric vehicle. In order to meet the power consumption device's requirements for high power and high energy density of the battery, a battery pack or a battery module may be used.
[0121] In some other specific examples, the power-consuming device may be a mobile phone, a tablet computer or a laptop computer. The power-consuming device is usually required to be light and thin, and may use a battery cell as a power source.
[0122] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0123] Example 1
[0124] 1) Preparation of sodium-containing positive electrode materials
[0125] MnO, Fe2O3, NiO and Na2CO3 were mixed in a molar ratio of Mn / Fe / Ni / Na of 1 / 3:1 / 3:1 / 3:1.03, and then placed in a sagger in a box furnace and sintered at 900℃ for 15h. After sintering, the mixture was cooled to room temperature and crushed to obtain NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 Sodium-containing cathode materials for O2.
[0126] 2) Alumina (D50 = 20 nm) and diammonium phosphate (D50 = 5 μm) were mixed in a ball mill at a molar ratio of Al to P of 0.4, the speed was controlled at 1000 rpm, and the ball milling was performed for 1 hour to obtain a composite coating agent.
[0127] 3) 1 kg of sodium-containing positive electrode material and 5 g of composite coating agent (coating amount is 0.5%) are mixed by a mechanical fusion machine, the mixing speed is controlled to 800 rpm, the mixing time is 0.5 h, the obtained mixed product is placed in a muffle furnace and sintered at 350 ° C for 8 h, and dry air is introduced during the sintering process. After the sintering is completed, it is naturally cooled to room temperature to obtain a sodium ion battery positive electrode material with a surface coated with a phosphate metal salt containing Na and Al. The morphology of the sodium ion battery positive electrode material is as follows Figure 1 As shown, the morphology of the sodium-containing positive electrode material (uncoated) is shown. Figure 2 In comparison, the surface of the sodium ion battery positive electrode material of Example 1 is dispersed with more and smaller particles, and the surface roughness of the material is higher, while the surface of the uncoated sodium-containing positive electrode material is relatively smooth.
[0128] Embodiment 2-6
[0129] The sodium ion battery positive electrode material was prepared according to the method of Example 1, except that in Examples 2-6, the amounts of aluminum oxide and diammonium phosphate were adjusted according to the Al / P molar ratios of 0.1, 0.3, 0.6, 1 and 8, respectively.
[0130] Examples 7-10
[0131] The sodium ion battery positive electrode material was prepared according to the method of Example 1, except that in Examples 7-10, the coating amount (the percentage of the mass of the composite coating agent to the mass of the substrate) was adjusted to 0.1%, 0.2%, 2% and 5%, respectively.
[0132] Examples 11-14
[0133] The sodium ion battery positive electrode material was prepared according to the method of Example 1, except that in Examples 11-14, the sintering temperatures were adjusted to 100° C., 300° C., 600° C. and 900° C., respectively.
[0134] Examples 15-18
[0135] The sodium ion battery positive electrode material was prepared according to the method of Example 1, except that in Examples 15-18, the sintering time was adjusted to 1 h, 3 h, 10 h and 20 h, respectively.
[0136] Comparative Example 1
[0137] The sodium-containing positive electrode material prepared in Example 1 was used as a comparative sample.
[0138] Comparative Example 2
[0139] A sodium ion battery positive electrode material was prepared according to the method of Example 1, except that aluminum oxide was not used and 5 g of ammonium dihydrogen phosphate was used as a coating agent.
[0140] Comparative Example 3
[0141] A sodium ion battery positive electrode material was prepared according to the method of Example 1, except that ammonium dihydrogen phosphate was not used and 5 g of aluminum oxide was used as a coating agent.
[0142] Embodiment 19
[0143] Alumina (D50=20nm), diammonium dihydrogen phosphate (D50=5μm) and titanium oxide (D50=30μm) were mixed on a ball mill at a molar ratio of Al / P / Ti of 0.4 / 1 / 0.2, the speed was controlled at 1000rpm, and the ball milling was performed for 1h to obtain a composite coating agent.
[0144] 1 kg of sodium-containing positive electrode material (same as in Example 1) and 5 g of a composite coating agent were mixed by a mechanical fusion machine, the mixing speed was controlled to be 800 rpm, the mixing time was 0.5 h, and the resulting precursor was placed in a muffle furnace and sintered at 350 ° C for 9 h, and dry air was introduced during the sintering process. After the sintering was completed, it was naturally cooled to room temperature to obtain a sodium ion battery positive electrode material having a surface coated with a phosphate metal salt containing Na, Al and Ti.
[0145] Embodiment 20
[0146] Alumina (D50 = 20 nm), diammonium phosphate (D50 = 5 μm) and calcium oxide (D50 = 50 μm) were mixed in a ball mill at a molar ratio of Al / P / Ca of 0.4 / 1 / 0.2, the speed was controlled at 1000 rpm, and the ball milling was performed for 1 hour to obtain a composite coating agent.
[0147] 1 kg of sodium-containing positive electrode material (same as in Example 1) and 5 g of a composite coating agent were mixed by a mechanical fusion machine, the mixing speed was controlled to be 800 rpm, the mixing time was 0.5 h, and the resulting precursor was placed in a muffle furnace and sintered at 400 ° C for 8 h, and dry air was introduced during the sintering process. After the sintering was completed, it was naturally cooled to room temperature to obtain a sodium ion battery positive electrode material having a surface coated with a phosphate metal salt containing Na, Al and Ca.
[0148] The composite coating agents and their amounts and sintering conditions in Examples 1-20 and Comparative Examples 1-3 are shown in Table 1.
[0149] Test Section
[0150] 1. Material Characterization
[0151] (1) Matrix crystal structure test
[0152] The Brucker D8A_A25 X-ray diffractometer from Brucker AxS, Germany, was used, with CuKα radiation as the radiation source and a wavelength of The sodium-containing positive electrode material was tested by scanning the 2θ angle range of 10°-90° and the scanning rate of 2° / min.
[0153] (2) Particle size (Dv50) test
[0154] The particle size test was carried out using a Malvern laser particle size analyzer, and the reference standard was GB / T19077-2016.
[0155] Pretreatment: Add an appropriate amount of the sample to be tested and water into a beaker, and add a dispersant (sodium hexametaphosphate), and ultrasonically disperse for 5 minutes at 120W to ensure that the sample is completely dispersed in the dispersant.
[0156] Test: After the sample is poured into the injection tower, it circulates with the solution to the test optical system. When the particles are irradiated by the laser beam, the particle size distribution characteristics of the particles are obtained by receiving and measuring the energy distribution of the scattered light (shading degree: 8-12%).
[0157] (3) Test of coating layer element content
[0158] First, the element binding energy and chemical shift of the sample surface are measured by XPS to obtain the element composition and chemical state of the sample surface, and then the element content is measured by inductively coupled plasma atomic emission spectroscopy.
[0159] (4) Test of coating thickness
[0160] The thickness of the coating layer was detected using a high-resolution transmission electron microscope (HR-TEM JEM-2100F).
[0161] (5) Scanning electron microscope (SEM) test
[0162] The test was carried out using a field emission scanning electron microscope (Zeiss Gemini360) according to the JY / T010-1996 standard.
[0163] The material characterization results are shown in Table 1.
[0164] 2. Performance Testing
[0165] (1) Preparation of button-type sodium ion batteries
[0166] 1) Preparation of positive electrode
[0167] The sodium ion battery positive electrode material prepared in the embodiment and the comparative example was respectively mixed with the conductive agent carbon black SuperP, the binder PVDF and the solvent NMP in a mass ratio of 80:15:5:100 and stirred evenly to obtain a positive electrode slurry; the positive electrode slurry was then evenly coated on one surface of the positive electrode collector (aluminum foil), and then dried, cold pressed and cut to obtain a positive electrode sheet.
[0168] 2) Preparation of negative electrode sheet
[0169] The negative electrode material hard carbon, the conductive agent carbon black SuperP, the binder CMC and the solvent water are mixed and stirred in a mass ratio of 8:1:1:10 to obtain a negative electrode slurry; the negative electrode slurry is then evenly coated on one surface of the negative electrode collector (copper foil); and then dried, cold pressed and cut to obtain a negative electrode sheet;
[0170] 3) Preparation of electrolyte
[0171] Sodium hexafluorophosphate (NaPF6) was dissolved in the solvent EC / DEC (1:1, v / v) to obtain a NaPF6 electrolyte with a concentration of 1 mol / L.
[0172] 4) The positive electrode sheet, separator (porous polyethylene film), and negative electrode sheet obtained above are cut into round pieces and arranged in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and the separator is infiltrated with the above electrolyte, and a button-type sodium ion battery is obtained after compaction.
[0173] (2) Performance test of sodium ion batteries
[0174] 1) Rate performance test
[0175] The rate performance test process is as follows: at 25°C, in the voltage range of 1.5-4.2V, the button sodium ion battery is charged and discharged at rates of 1C and 5C respectively, and the capacity of the material at rates of 1C and 5C can be obtained, with a nominal specific capacity of 140mAh / g.
[0176] 2) 400-cycle capacity retention rate
[0177] The cycle performance test process is as follows: at 25°C, charge the button sodium ion battery to 4.2V at a rate of 0.1C, and then discharge it to 1.5V at a rate of 0.1C. Repeat this process once to complete the activation of the battery. After activation is completed, charge the button sodium ion battery to 4.2V at a rate of 1C, and then discharge it to 1.5V at a rate of 1C. At this time, the initial capacity of the cycle is obtained. Repeat the above 1C charge and discharge system 400 times. The 400-cycle capacity retention rate can be obtained by dividing the 400-cycle discharge capacity by the first 1C discharge capacity.
[0178] 3) Electrochemical impedance spectroscopy (EIS) test
[0179] The German Zahner electrochemical workstation was used for testing. The Zview software was used to fit the impedance information of the high-frequency, medium-frequency and low-frequency regions according to the equivalent circuit to determine the Rct and R s The impedance value setting frequency is 100kHz-0.01Hz, and the voltage amplitude is set to 10mV.
[0180] The EIS test process is as follows: the button sodium ion battery is charged and discharged at a rate of 0.1C in the voltage range of 1.5-4.2V for one week, and then charged to 4.2V at a rate of 1C and constant voltage until the current is less than or equal to 0.05C, and then the EIS test is performed after standing for 6 hours.
[0181] 4) Na + Diffusion coefficient test
[0182] Na + The diffusion coefficient test process is as follows: At 25°C, the button sodium ion battery is charged to 4.2V at a current density of 10mA / g, and then discharged to 1.5V at a current density of 10mA / g. The sodium ion diffusion coefficient (DNa+) is calculated as follows:
[0183] D Na+ =R 2 T 2 / (2A 2 n 4 F 4 C 2 σ 2 ) Formula 1
[0184] Z′=R s +R ct +σw -1 / 2 Formula 2
[0185] Where R is the gas constant, R = 8.314 J / (mol·K). T = 298 K, A is the electrode area (1.54 cm 2 ), n is the number of electrons transferred during the reaction (n = 1), F is the Faraday constant, C is the bulk concentration of sodium ions, C = ρ / M (ρ is the density of the positive electrode material, M is the molar mass of the material), σ is the slope of the impedance fitting of formula 2, and substituting it into formula 1 can calculate Na + Diffusion coefficient;
[0186] In formula 2, Z' represents Warburg impedance, Rct represents charge transfer impedance, R s represents the interface film impedance, and w represents the angular frequency.
[0187] The test results of the button cells prepared above are shown in Table 2.
[0188] Table 1
[0189]
[0190]
[0191] Table 2
[0192]
[0193]
[0194] Comparing Examples 1-20 with Comparative Example 1, it can be seen that the batteries prepared by the sodium ion battery positive electrode materials of Examples 1-20 have higher 5C capacity, capacity retention rate and Na + It can be seen that compared with the sodium-containing electrode material without a coating layer (Comparative Example 1), the positive electrode material prepared by co-coating with the coating raw material containing the solid phosphorus source and the solid aluminum source in Examples 1-20 can improve the battery's rate performance, cycle stability and Na + In Comparative Examples 2 and 3, although the sodium-containing positive electrode material was coated with a phosphorus source and an aluminum source respectively, the rate performance of the prepared positive electrode material was poor. + The diffusion coefficient is low.
[0195] Figure 3 The figure shows the change in capacity retention rate of the batteries of Example 1 and Comparative Example 1 during 400 cycles. It can be seen from the figure that the capacity retention rate of the battery of Example 1 is always higher than that of Comparative Example 1, and as the number of cycles increases, the rate of decrease of the capacity retention rate is also much lower than that of Comparative Example 1, indicating that the battery of Example 1 has higher stability.
[0196] In summary, the present application modifies the sodium-containing positive electrode material with a coating raw material containing a phosphorus source and an aluminum source, and the phosphate containing at least sodium and aluminum formed on the surface of the substrate simultaneously improves the conductivity and cycle stability of the positive electrode material.
[0197] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A sodium ion battery positive electrode material, characterized in that: include: A sodium-containing positive electrode material matrix, and a coating layer coated on at least a portion of the surface of the sodium-containing positive electrode material matrix; wherein the coating layer comprises a metal phosphate, and the metal phosphate contains at least sodium and aluminum elements.
2. The sodium ion battery positive electrode material according to claim 1, characterized in that The chemical formula of the metal phosphate is Na x1 Al y1 L y2 P z O s , wherein L includes at least one of Ca, Mg, Fe, Ti, V, Cr, Mn, Ni, La, Ce, Sr, Cu, Zn, Y, Zr, Nb and Mo; x1>0, y1>0, y2≥0, z>0, s>0; Optionally, the chemical formula of the metal phosphate is NaAl y1 L y2 P z O2, and 0<y1<1, 0≤y2<1, 0<z<1.
3. The sodium ion battery positive electrode material according to claim 1 or 2, characterized in that In the metal phosphate, the molar ratio of aluminum element to phosphorus element is 0.1-10, and can be optionally 0.1-0.
6.
4. The sodium ion battery positive electrode material according to any one of claims 1 to 3, characterized in that The coating layer has a thickness of 1 nm-100 nm, and can be optionally 5 nm-25 nm.
5. The sodium ion battery positive electrode material according to any one of claims 1 to 4, characterized in that: The sodium-containing positive electrode material matrix includes a layered oxide, the chemical formula of which is Na x2 Mn a Fe b M c A d O 2-e+f Q e , wherein M includes at least one of Cu, Ni, Li, Ti, Zr, K, La, Ce, Sr, Sb, Nb, Mg, Ca, Mo, Zn, Cr, W, Bi, Sn, Ge and Al; A includes at least one of Si, P, B, S and Se; Q includes at least one of F, Cl and N; a>0, b>0, c≥0, d≥0, and a+b+c+d=1, x2≥0.66, 0≤e≤0.1, -0.1≤f≤0; Optionally, the layered oxide is an O3 type layered oxide.
6. The sodium ion battery positive electrode material according to any one of claims 1 to 5, characterized in that: The mass ratio of the coating layer to the sodium-containing positive electrode material matrix is (0.1-10):100, and can be optionally (0.2-2):
100.
7. A method for preparing the sodium ion battery positive electrode material according to any one of claims 1 to 6, characterized in that: include: The coating layer raw materials including the aluminum source and the phosphorus source are mixed with the sodium-containing positive electrode material matrix and sintered.
8. The method according to claim 7, characterized in that The aluminum source comprises at least one of aluminum oxide and aluminum hydroxide; and / or The phosphorus source includes at least one of diammonium phosphate and ammonium metaphosphate.
9. The method according to claim 7 or 8, characterized in that: The aluminum source is aluminum oxide, and the median particle size of the aluminum oxide is 10nm-50nm; the phosphorus source is ammonium dihydrogen phosphate, and the median particle size of the ammonium dihydrogen phosphate is 1μm-15μm.
10. The method according to any one of claims 7 to 9, characterized in that: The sintering satisfies at least one of the following conditions: (1) The sintering temperature is 100°C-1000°C, and can be 300°C-600°C; (2) The sintering time is 1h-24h, and can be optionally 3h-10h.
11. The method according to any one of claims 7 to 10, characterized in that: The mixing comprises the following steps: The components in the coating layer raw material are first mixed to obtain a composite coating agent; performing a second mixing of the composite coating agent and the sodium-containing positive electrode material matrix; Optionally, the first mixing conditions include: a rotation speed of 800 rpm-1200 rpm, and a time of 20 min-60 min; Optionally, the second mixing conditions include: a rotation speed of 800 rpm-1000 rpm, and a time of 20 min-30 min.
12. The method according to any one of claims 7 to 11, characterized in that: The coating layer raw material also includes at least one of titanium oxide and calcium oxide.
13. A positive electrode sheet, characterized in that: A sodium ion battery positive electrode material comprising the sodium ion battery positive electrode material according to any one of claims 1 to 6 or a sodium ion battery positive electrode material prepared by the method according to any one of claims 7 to 12.
14. A battery, characterized in that: A sodium ion battery positive electrode material comprising any one of claims 1 to 6 or a sodium ion battery positive electrode material prepared by the method of any one of claims 7 to 12, or a positive electrode sheet comprising the positive electrode sheet of claim 13.
15. An electrical device, characterized in that: Comprising the battery of claim 14.
Citation Information
Patent Citations
Controllable epitaxial sodium ion battery positive electrode material, preparation method thereof and sodium ion battery
CN114597363A
Composite positive electrode material, preparation method and application thereof, sodium ion battery, sodium ion battery pack and equipment
CN114824269A
Sodium-ion battery positive electrode material as well as preparation method and application thereof
CN115411258A
Sodium ion positive electrode material, preparation method and application thereof, sodium ion battery, sodium ion battery pack and equipment
CN116190657A
Sodium battery cathode active material and method of producing the same
JP2015018621A
Cited By
Composite phosphate coated high-voltage sodium-electrode layered oxide positive electrode material and preparation method thereof
CN121076112A
